المهارات الاتصالية للقادة التربويين ودافعية المعلمين بمدارس أساس محلية أم درمان - Nasser Habtoor; Abdul Latif Al-Fadni (Design for Scientific Renaissance Sdn Bhd, 2024)
This study aimed to find a relationship between the communicative skills of the educational leaders and teachers’ motivation, from the point of view of teachers in the schools of Omdurman; the researcher opted fora stratified random sample, represented in the study population consisting of 329 male and female teachers in 43 elementary schools in Omdurman. For this purpose, the researcher used a questionnaire with two themes, the first to measure the communicative skills of the educational leaders, which items had been taken from previous studies, then submitted to some specialized lecturers to consider their views and observations; the items were modified and improved to suit the current study. This first theme is composed of 18 items assigned to four communicative skills which are: listening, conversing, writing, and communication through personal interviews. The second theme was to measure the role of the educational leaders in the motivation of teachers, and is made up of 10 items dispensed to the areas of: working in a team and motivation and encouragement; consistency and validity of the questionnaire were established. The results of the study showed that the conversation skill topped the ranking of the educational leaders’ communicative skills, whereby it recorded a percentage of 70%; this result suggests that the educational leaders in the elementary schools of the locality of Omdurman prefer conversation in their communication with teachers. The skill of communication through personal interviews came in second with a percentage of 69.4%; which is an average result. The skill of listening has also recorded a moderate rate, as represented by the proportion of 68.6%. The writing skill results of the analysis showed that the practice of writing by the educational leaders in their communication with the teachers was weak; it recorded a rate of 56.8%. The study also demonstrated a strong relationship between the communicative skills of the educational leaders and teachers' motivation. The study came out with a number of recommendations, most notably the interest in the development of teachers scientifically, practically and technically through the enhance mint of the educational leaders’ communicative skills and their training on these skills, especially the skill of writing; in addition the study recommended a research to determine the relationship between the communicative skills of the educational leaders and job satisfaction.